ANTIOXIDANT ACTIVITY OF THE TOPICAL PREPARATION OF BULUNG SANGU (Gracilaria spp) EXTRACT - Sasadara, Maria Malida Vernandes; Wirawan, I Gede Putu; Sritamin, Made; Suada, I Ketut; Adiartayasa, Wayan (International Journal of Biosciences and Biotechnology, 2020)
Bulung Sangu ( Gracilaria spp) as many other macroalgae, is a source of beneficial phytochemical for health. Phytochemicals in macroalgae are widely used as active ingredients in cosmetic preparations. The study was aimed to determine the antioxidant properties of Bulung Sangu formulated in topical preparation. Bulung Sangu was macerated in ethanol 96% following by extract formulation in cream preparation in two concentrations: 5% and 10%. Antioxidant activity was determined against DPPH radical, compared to ascorbic acid. Percentage of reducing power in five concentration series (10, 20, 30, 40, and 50 µm/ml) statistical analyzes using one-way ANOVA with 95% of confidence level, following by IC 50 measurement. Absorbance was read in wavelength of 517 nm. Concentration of 5% and 10% cream extract exhibited IC 50 of 13,091 µg/ml and 11,867 µg/ml, respectively. These values are lower than IC 50 of ascorbic acid (18,505 µg/ml), indicating the strong antioxidant properties of Bulung Sangu extract cream which is more potential than ascorbic acid. Bulung Sangu exhibit a potential source for being developed as medicine and cosmetics in topical preparation.